If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7v + -1 = 2v + 17 Reorder the terms: -1 + -7v = 2v + 17 Reorder the terms: -1 + -7v = 17 + 2v Solving -1 + -7v = 17 + 2v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '-2v' to each side of the equation. -1 + -7v + -2v = 17 + 2v + -2v Combine like terms: -7v + -2v = -9v -1 + -9v = 17 + 2v + -2v Combine like terms: 2v + -2v = 0 -1 + -9v = 17 + 0 -1 + -9v = 17 Add '1' to each side of the equation. -1 + 1 + -9v = 17 + 1 Combine like terms: -1 + 1 = 0 0 + -9v = 17 + 1 -9v = 17 + 1 Combine like terms: 17 + 1 = 18 -9v = 18 Divide each side by '-9'. v = -2 Simplifying v = -2
| (1/2)x+1-x=(3/5)(x-7/2)-1 | | -8v-6=-4v+2 | | 7(3o+5)= | | 3(-x-3)=-3(x+5)+6 | | X-10=.6(9-10x) | | x+55=x+135 | | 2(r-4)=3n-6+5 | | -3(p+1)+2=3(-p-3) | | 32=-3m+1 | | -11+46=-5(x+1) | | (x+8)-x-(5-6x)=15 | | 4z+5z=4z-5+6z | | -2(2b+3)+(5b-2)=0 | | (6x+3)(x-5)=9 | | 0.3x^3+0.4x^3-0.2x^3= | | 1.2x(6-5)=7 | | (6x+3)(x-5)=0 | | 3(x-2)=2(x-1) | | 7[9+16]=0 | | 11(k-2)+2[k-3(k+1)]=0 | | x-2=3x-12 | | 4x+7=2x-1 | | -4m+10+5m=14-4m | | 5x^4-2x^2+20x^2-8= | | 3+5+7=72 | | 5(3x+1)=3x-9x | | 2x+7=6x-9 | | 5(x+6)=5(x+2) | | 18x-2=10x-10 | | 10(f-3)=2(f-20)-50 | | (w-9)(w+16)=0 | | -6y-4=-5y-8 |